EDUCATING AND REHABILITATING THE CHILD AND YOUNG OFFENDERS IN THE PRISONS : A PRACTICE IN MALAYSIA - Taib, Rosfizah Md (International Business Education Journal, 2011)
The paper will analyse the data from interviews with the officials of the Malaysian establishments to show their attitudes in relation to the concept of rehabilitation applied to the child and young offenders. Thoughts and beliefs of the respondents regarding the importance of education and its role in rehabilitating the child and young offenders in the institutions are discussed. The paper will assess whether the attitudes of the officials towards understanding the importance of education influences the rehabilitation process for the child and young offenders in the institutions. In conclusion, the findings suggest that the officials believe education is the key underlying concept that would ensure the effective rehabilitation process for the child and young offenders in Malaysia.